Hip strength does not correlate with hip and knee biomechanics during single-leg tasks: A systematic review with meta-analysis and evidence gap map - Garcia, M. C.; Waiteman, M. C.; Taylor-Haas, J. A.; Bazett-Jones, D. M. (Journal of Sports Sciences, 2024)
We systematically reviewed and synthesized the evidence for the relationship between hip strength and hip and knee biomechanics during single-leg tasks in uninjured and injured populations. We searched CINAHL, EMBASE, PubMed, SportDiscus, and Web of Science from inception to July 2024. We included cross-sectional studies with uninjured and/or injured participants that reported correlations between hip strength and hip or knee kinematics during a single-leg task. We identified 41 articles that reported the correlations between hip strength and hip or knee kinematics during a single-leg task for uninjured (n = 33) and/or injured (n = 12) populations. We identified moderate-to-strong evidence for no-to-poor relationships between most hip strength and hip and knee kinematics during a single-leg task for uninjured (r = -0.33-0.45) and injured populations (r = -0.24-0.24). We observed limited-to-moderate evidence for fair-to-moderate negative relationships between concentric and eccentric hip abduction strength and hip adduction (r = -0.52) and knee abduction kinematics (r = -0.45-0.59) for uninjured populations. Isometric hip strength may not play as important of a role in controlling lower extremity motion during single-leg tasks as previously perceived, but isokinetic strength may be a better indicator of lower extremity motion during single-leg tasks.